2018
DOI: 10.1002/celc.201701299
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Tipped Au Nanorods for Plasmon‐Enhanced Electrocatalytic Hydrogen Evolution with Photoelectric and Photothermal Effects

Abstract: Plasmonic bimetallic structures have been wildly used in photocatalysis, owing to their tunable optical properties and desirable catalytic activities. However, it is still a challenge to realize the enhanced electrocatalytic hydrogen evolution reaction (HER) using these structures with electric, photo‐, and thermal effects. Herein, we report that Pd‐tipped Au nanorods (NRs) were prepared for electrochemical water splitting in the visible and near‐infrared region. The NRs exhibited a lower onset overpotential (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Recently, introducing thermal energy to promote electrocatalytic conversion has attracted significant interest (7)(8)(9)(10). The thermal energy could accelerate the motion of reactant molecules, promote their effective collisions during the reaction, and thus make it easier to overcome the activation barrier (11,12).…”
mentioning
confidence: 99%
“…Recently, introducing thermal energy to promote electrocatalytic conversion has attracted significant interest (7)(8)(9)(10). The thermal energy could accelerate the motion of reactant molecules, promote their effective collisions during the reaction, and thus make it easier to overcome the activation barrier (11,12).…”
mentioning
confidence: 99%
“…The plasmon-enhanced electrocatalytic activity may be ascribed to the hot electron transfer and the photothermal effect. 10,16,31 While the hot electron transfer can be enhanced by the local electromagnetic field enhancement, the photothermal effect can be promoted by the strong absorption in the NIR region. Therefore, the hierarchical Au/PdAg NRNSs adopt advantageous structural features for both electrocatalysis and plasmon-enhanced electrocatalysis, thus showing the best electrocatalytic and photoassisted electrocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…28 It is noteworthy that there are several reports on the synthesis and plasmon-enhanced catalysis of hierarchical Au-Pd heterostructures made of GNRs covered by 1D Pd nanostructures; examples include Au-Pd superstructures with ordered Pd nanoarrays precisely grown on GNRs for plasmonenhanced carbon-carbon coupling reactions, 29 Pd nanodendrite-tipped GNRs for plasmon-enhanced Suzuki cross-coupling reactions, 30 and Pd-tipped GNRs for plasmon-enhanced electrocatalytic hydrogen evolution. 31 Furthermore, Au@PdAg core-shell nanorods were obtained from conversion of Au@Pd core-shell nanorods. 32 Some hierarchical Au-PdAg heterostructures based on GNRs were synthesized through CTABassisted overgrowth on GNRs 33 and conversion of Au@Ag core-shell nanorods, 34,35 and their applications in electrocatalytic ethanol oxidation were explored.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to increase the performance of a catalytic system is via the incorporation of special metal nanostructures, such as metal-tipped, porous, or needle-like plasmonic structures that have a high electrochemical surface area. Wei et al recently proposed plasmonic bimetallic structures based on Pt-tipped Au nanorods (Au NRs) for electrochemical water splitting in the visible and the near-infrared region [32]. They demonstrated that these nanostructures outperformed fully Pt-covered nanostructures, which show weak LSPR bands.…”
Section: Synthesis Of Plasmonic Electrocatalysts: From Single To Mmentioning
confidence: 99%